Predictive value of telomere length on outcome following acute myocardial infarction: Evidence for contrasting effects of vascular vs. blood oxidative stress - Margaritis, M; Sanna, F; Lazaros, G; Akoumianakis, I; Patel, S; Antonopoulos, A; Duke, C; Herdman, L; Psarros, C; Oikonomou, E; Shirodaria, C; Petrou, M; et al. (Oxford University Press, 2017)
Aims: Experimental evidence suggests that telomere length (TL) is shortened by oxidative DNA damage, reflecting biological aging. We explore the value of blood (BTL) and vascular (VTL) TL as biomarkers of systemic/vascular oxidative stress in humans and test the clinical predictive value of BTL in acute myocardial infarction (AMI). Methods and Results: In a prospective cohort of 290 patients surviving recent AMI, BTL measured on admission was a strong predictor of all-cause (HR[95%CI]: 3.21[1.46-7.06], P=0.004) and cardiovascular mortality (HR[95%CI]: 3.96[1.65-9.53], P=0.002) 1 year after AMI (for comparisons of short versus long BTL, as defined by a T/S ratio cut-off of 0.916, calculated using ROC analysis; P adjusted for age and other predictors). To explore the biological meaning of these findings, BTL was quantified in 727 consecutive patients undergoing coronary artery bypass grafting (CABG), and superoxide (O2 .- ) was measured in peripheral blood mononuclear cells (PBMNC). VTL/vascular O2 .- were quantified in saphenous vein (SV) and mammary artery (IMA) segments. Patients were genotyped for functional genetic polymorphisms in P22phox (activating NADPH-oxidases) and vascular smooth muscle cells (VSMC) selected by genotype were cultured from vascular tissue. Short BTL was associated with high O2 .- in PBMNC (P=0.04) but not in vessels, whereas VTL was related to O2 .- in IMA (rho=-0.49, P=0.004) and SV (rho=-0.52, P=0.01). Angiotensin II (AngII) incubation of VSMC (30 days), as a means of stimulating NADPH-oxidases, increased O2 .- and reduced TL in carriers of the high-responsiveness P22phox alleles (P=0.007) Conclusion: BTL predicts cardiovascular outcomes post-AMI, independently of age, whereas VTL is a tissue-specific (rather than a global) biomarker of vascular oxidative stress. The lack of a strong association between BTL and VTL reveals the importance of systemic vs. vascular factors in determining clinical outcomes after AMI.